Estudio productivo y económico del cultivo del plukenetia volubili (sacha inchi, maní indio) en la parroquia Jambelí, cantón, Lago Agrio provincia de Sucumbíos - Villalba Cando, Gloria Piedad (2014)
The “Sacha inchi “is an oil of Euphorbiaceae family is distributed throughout the Amazon wild. Special note for which is found in the Northeast Ecuadorian and has been adopted as a crop agriculture over the Amazon . Why is being grown in the parish of Canton Lake Jambelí Agro Sucumbíos Province as a new agronomic alternadita improve family income , for traditional crops such as corn , beans , sugar cane , banana, etch . , Which when no longer profitable for the economy of the farmer. For when there have greater access to consumer markets, the number of food imports that currently exist at the expense of domestic production prices. This oily , which originally existed only in the Amazon, in the wild and is considered an ancestral plant with large food and medicinal benefits , currently according to research that has been carried on it, shows his value food , nutrition and health principles assets , having great success in the local and global market. Acceptance to be because the chemical composition containing : oils rich in essential fatty acids , Omega 3 and Omega 6, as well as other protein components , which has enabled it to be a product used for human consumption and preparation of food rations animal . Special features that encouraged the growth of this crop in a technical way , because to have a good 6 price and market, improve the income of traditional crops , so parish Jambelí Canton Sucumbios is this , considering that to be a new crop in rural areas this study is needed to characterize the power . Sacha inchi in existing crops, make their economic performance , see their marketing and have the technical and business knowledge to promote it as a new sustainable agricultural productive option ecologically and economically viable to develop the sector. The methodology used in the study was based on the review of available literature about the culture there and fieldwork , which consisted in visiting the farms of the producer , dedicated to cultivation in the parish Jámbeli . As well as taking as a reference for obtaining and validating technical and accounting information, Arciniega Villa, which is one of the most representative crop in the area, The results indicate the characteristics , chemical and physiological characteristics of this crop , which is being adapted to a modernized agricultural system in order to have access to international markets . Also we note that the Sacha Inchi in the study area , is characterized by an Amazonian naturally oily , adapting to new farming methods , which is a product with great national and international acceptance , to possess , nutritional food properties and healing for humans . As well as their primary and industrialized products are used for animal feed and for formulating rations as balanced animal , because of its protein content. 7 Marketing sacha inchi, middle , shows us that the product is sold in its highest percentage in the basic form that is roasted beans similar to peanuts, which are expended in the sector from producers to intermediaries . Fulfilling the farmer in the marketing chain functions , producer and gatherer , because they perform their fortnightly crops , which are then sold to intermediaries in the sector, which in turn have contacts with international companies that buy grain, for processing and industrialization . With this marketing method established, there is a periodic marketing , with which the farmer gets current revenues , which help stabilize its economy, your family and in turn the industry , and capitalizing the agricultural sector. The financial study , was established in his analysis of the financial statements of the Finch Arciniega , because in the primary or agricultural industry , this type of analysis is a valuable tool to learn about the operations of a business and have a simple information quick , that allows the producer decision making , because knowledge of these indices allows the administrator to take agriculture , important decisions quickly control , planning and project studios The accounting information, set out in this study with the construction of the same , through the accounts of l Arciniega estate inventory after obtaining the balance sheet , which we agreed to calculate the various financial indicators , as Liquidity Index , solvency, equity , debt, etc. . , applying mathematical 8 relations in the general accounts, which did not provide information, clear, direct and understandable for farmers. Similarly , we build profit and loss, which gave us the indices that indicate that the revenue from the sale of dried seeds of Sacha Inchi in Ha average about $ 8,280 , oo , leaving net income this crop total is $ 5.407.40 , with a cost benefit ratio of 2.88 % , a percentage of ROI 188.2 %. Positive indicators to stabilize the rural economy So we recommend to continue this type of cultivation steadily and associating with primary food crops. And strengthen the existing organization and the organizations foramen producer Sacha inchi in Jámbeli parish, for the farmer , which is gatherer grain , whoever negotiates directly with agribusiness companies or form their own Amazon enterprises , improving and their income .